Proceedings of essential health care package development, in Botswana and Sierra Leone, November 2022 - Humphrey Cyprian Karamagi; Solyana Ngusbrhan Kidane; Pierre Claver Kariyo; Araia Berhane Mesfin; Isabella Maina; Gertrude Avortri; Hyppolite Kalambay Ntembwa (BMC Proceedings)
Abstract The development of essential health care package (EHCP) has been recognized as a critical tool for guiding country level actions towards Universal Health Coverage (UHC). Although countries’ packages vary in scope, many utilize the package to guide resource allocation, equity, advocacy, prioritization of services, political commitment, and accountability. The concept of health packages has evolved from basic packages (focusing on limited high-burden conditions), to benefit- (cost-effective interventions) and essential packages (what people need, with benefits as sub-packages). The purpose of this proceeding was to document processes from Botswana and Sierra Leone workshops, which aimed to support country conceptualization of an EHCP, including content and scope. More specifically, the workshop aimed to gain consensus on identification of conditions to be addressed in each age cohort, rationalizing the EHCP interventions across public health functions, levels of care and age cohorts. Technical working groups were constructed for each age cohort and tasked to lead the appraisal of interventions for technical comprehensiveness, contextualization to country needs, and mapping of interventions to the appropriate levels of care. As a result, the countries' draft EHCPs were developed, encompassing interventions for 80 + conditions. The EHCP is expected to set precedence in defining ‘essential’ interventions for the population, structurally promoting integration of health services, and providing succinct guidance to partners, and stakeholders on the country's priorities, in terms of health interventions to be delivered at various levels. Many countries are striving to re-pivot their health systems, in order to meet the evolving contextual needs of the population and ensure their systems remain fit for purpose. EHCPs can be utilized to guide health sector inputs, for robust system functionality and attainment of UHC.